2021
DOI: 10.1080/09537325.2021.1901875
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between technological improvement and innovation diffusion: an empirical test

Abstract: Different technological domains have significantly different rates of performance improvement. Prior theory indicates that such differing rates should influence the relative speed of diffusion of the products embodying the different technologies since improvement in performance during the diffusion process increases the desirability of the product diffusing. However, there has not been a broad empirical attempt to examine this effect and to clarify the underlying cause. Therefore, this paper reviews the theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The first telematics systems were launched in the early 1990s and are now standard components on most new vehicles sold. It is hard not to notice that electrification technologies improve slowly and have slower adoption rates while automated/ autonomous and connectivity-related technologies are improving faster and also have higher adoption rates, This relationship between improvement rates and adoption supports the conclusion byWoo and Magee (2018) suggesting that technologies improving at a faster rate have a faster adoption rate especially during their infancy.CHAPTER 5: CONCLUSIONSThis work reviews past work on technological forecasting and decision making and builds on new research to introduce a systematic approach to technological decision-making. We describe the development of a new web-based technology search tool and apply the methodology to a case study of the automotive industry.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…The first telematics systems were launched in the early 1990s and are now standard components on most new vehicles sold. It is hard not to notice that electrification technologies improve slowly and have slower adoption rates while automated/ autonomous and connectivity-related technologies are improving faster and also have higher adoption rates, This relationship between improvement rates and adoption supports the conclusion byWoo and Magee (2018) suggesting that technologies improving at a faster rate have a faster adoption rate especially during their infancy.CHAPTER 5: CONCLUSIONSThis work reviews past work on technological forecasting and decision making and builds on new research to introduce a systematic approach to technological decision-making. We describe the development of a new web-based technology search tool and apply the methodology to a case study of the automotive industry.…”
mentioning
confidence: 61%
“…Identifying a technology "just" when it's about to take-off in the S-curve model of diffusion and investing significantly in product development, marketing/ sales at that time, can allow a firm to gain market share quickly and establish a "dominant design" (Benson & Magee, 2018). In addition, there is evidence that faster improving technologies are also adopted at a faster rate during their infancy (Woo & Magee, 2018). This can allow for more accurate estimates of expected sales during the infancy of a technology and can provide a guide for creating realistic technology development and sales roadmaps.…”
Section: Figure 1 Technology Improvement and Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the positive increase, there is a reduction in both the log gross margin and farm productivity of the very high-level users. This was expected since the effect of innovation on competitiveness at the latter stage is tempered by saturation effects hence the decrease (Woo & Magee, 2017) in the competitive level of the agrienterprises.…”
Section: Mean Potential Outcome Across the Treatment Effectsmentioning
confidence: 99%
“…Foster [26] posited the theory of S-curves and suggested that technologies evolve along successive S-curves. The latter has become the canonical representations of the technology's life cycle [37,64]. Traditional researches mainly focus on one performance dimension (e.g., high or low) to consider the smooth substitution between two technologies [32,55].…”
Section: Literature On Technology Diffusion and Adoptionmentioning
confidence: 99%